1994
DOI: 10.1002/depr.3050020307
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclics and newer antidepressant medications: Treatment options for treatment‐resistant depressions

Abstract: Only about 60-70% of those depressed patients who can tolerate an antidepressant medication, and only about SO-60% of those who begin a medication will respond to the Frst trial. Furthemnore, S-10% will remain depressed despite multiple medication trials. When the disorder is poorly responsive, it is variously described as a resistant, refractory, or intractable depression. This review summarizes the available literature on treatment-resistant depression (TRD) to provide recommendations for the most rational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 152 publications
(163 reference statements)
0
10
0
1
Order By: Relevance
“…Treatment-resistant depression (TRD) is defined as failure to respond to two adequate medication trials or as a relapse during treatment [7]. The STAR*D trial showed that 60 % of patients with MDD fail to respond to two antidepressant trials of optimal dose and duration, while a further 30 % failed to respond to four medication trials [8].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment-resistant depression (TRD) is defined as failure to respond to two adequate medication trials or as a relapse during treatment [7]. The STAR*D trial showed that 60 % of patients with MDD fail to respond to two antidepressant trials of optimal dose and duration, while a further 30 % failed to respond to four medication trials [8].…”
Section: Introductionmentioning
confidence: 99%
“…"Treatment resistant depression" is a descriptive term that implies failure of the depression to respond to treatment [Baldwin and Simpson, 1997]. However, there is no general consensus regarding criteria for treatment resistance [Guscott and Grof, 1991;Thase et al, 1994Baldwin and Simpson, 1997]. Some authors have suggested that failure to respond to one antidepressant drug given at an adequate dose for a sufficient length of time constitutes treatment resistance, whereas others have used a more stringent definition [Guscott and Grof, 1991;Thase et al, 1994Baldwin and Simpson, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no general consensus regarding criteria for treatment resistance [Guscott and Grof, 1991;Thase et al, 1994Baldwin and Simpson, 1997]. Some authors have suggested that failure to respond to one antidepressant drug given at an adequate dose for a sufficient length of time constitutes treatment resistance, whereas others have used a more stringent definition [Guscott and Grof, 1991;Thase et al, 1994Baldwin and Simpson, 1997]. In the absence of consensus criteria for treatment resistance, we adopted a conservative approach (8 weeks of a tricyclic including 2 weeks of adjunctive lithium) so as to increase the chance of including patients who were truly refractory to treatment and decrease the chance of including patients who were simply having a delayed response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported increased rates of psychiatric comorbidity after interpersonal trauma (Kessler et al, 1995), underdiagnoses in physician practices, underestimates of burden of distress and impairment (Kendler, Gardner, & Prescott, 2002; Mayou & Farmer, 2002), and increased hospitalization for poor treatment response (Firsten, 1991; Thase, Rush, Kasper, & Nemeroff, 1995). Depression associated with histories of CSA often carries with it severe psychological burden, a protracted longitudinal course, and an increased risk of poor treatment response to antidepressant therapy (Boudewyn & Liem, 1995; Hall, Sachs, Rayens, & Lutenbacher, 1993).…”
Section: The Health Effects Of Interpersonal Traumamentioning
confidence: 99%